Transformation Of Political Participation In The Digital Age, The Role Of Social Media In Shaping Public Opinion And Mass Mobilization - Ariestandy, Denny; Adidharma, Wawang; Isdendi, Rio Razab (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
In the digital era, social media has become a significant tool in redefining how Society participates in politics. Platforms like Facebook, Twitter, and Instagram enable individuals and groups to voice their opinions, organize movements, and influence public policy more directly and swiftly than traditional media. This study aims to examine the transformation of political participation in the digital age, focusing on the role of social media in shaping public opinion and mass mobilization. The research method used in this study is a literature review. The research finds that social media has the power to expand the reach of political participation, especially among younger generations and marginalized groups who were previously difficult to engage through traditional political channels. However, this study also highlights several challenges, including spreading misinformation, opinion polarization, and the risk of political manipulation through social media algorithms. In conclusion, social media has great potential to transform political participation, but it also requires a cautious approach to managing its negative impacts. Further research is needed to understand how policies can be adapted to this new reality to ensure more inclusive and healthy political participation in the digital age.